Evolution of large arroyos: the Rio Puerco of New Mexico - Elliott, John G. (John Grant), 1951-, author; Schumm, Stanley Alfred, 1927-, advisor; Morris, Elizabeth Ann, 1932-, committee member; Ethridge, Frank G., committee member (Colorado State University. Libraries, 1979)
Since the inception of widespread erosion in the southwestern United States nearly a century ago, sufficient time has elapsed for many long-term adjustments in channel and arroyo form to become perceptible. Geomorphic and hydrologic changes indicate that the Rio Puerco of northwestern New Mexico is adjusting its morphology to new equilibrium conditions. The width of the formerly trench-like arroyo has been greatly increased, and the creation of a new flood plain today gives the arroyo a valley-like character along most of its lower course. Morphological variations up and downstream are due to different stages of arroyo development, and therefore, areal differences have been drawn upon to illustrate temporal progression of the evolutionary process. Host of the arroyo today is characterized by one of two geomorphic phases. The arroyo of Type 1 reaches is broad and flat bottomed, and it is actively widened by periodic shifting of the sediment laden channel flowing within. Along Type 2 reaches the arroyo is more mature in its development, having an inner-flood plain and a relatively stable channel. Following rejuvenation of its tributaries, the evolution of a large arroyo continues with lateral erosion of valley fill because the sediment burdened channel is prone to abrupt shifts in position and pattern. Under these conditions arroyo width continues to increase until a geometry conducive to efficient transport of flood waters without excessive erosion of valley fill is attained. As tributaries mature, a reduction in mean annual discharge, peak annual flood and bedload transport with deposition of suspended sediment and establishment of riparian vegetation all tend to reduce the width of the channel within the arroyo and stabilize its banks. Evolution of the arroyo continues with modification of the new inner-flood plain, as a sinuous channel is formed which proceeds to meander through alluvial deposits. Today, upper reaches of the Rio Puerco's arroyo are still being actively widened but the broad, vegetated valley phase of evolution characterizes most lower reaches of the valley. Therefore, there is an evolutionary sequence in an upstream direction.
Keywords: Arroyos -- Puerco River (N.M. and Ariz.)